ANALISIS BIAYA DAN PENDAPATAN USAHATANI KEDELAI DI KABUPATEN SUKOHARJO - UMI BAROKAH (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2011)
The objectives of this research are to analyze the revenue, cost and income of soybean farm in Sukoharjo Regency, reached the highest economic efficiency. The main method of this research was descriptive. The research was conducted in Sukoharjo Regency and taken 30 farmers as the sample. The samples are monoculture soybean farmer which selected by purposive sampling. The result shows that average cost of the soybean farmer was Rp 3.947.131,58/ha, the average revenue Rp 10.509.794,74 / ha and average income was Rp 6.562.663,16 / ha.